(untitled) (Research, Society and Development, 2022)
This article reveals a theoretical research that dialogues about the Life Project proposed by the 2018 National Common Curriculum Base of High School, whose emphasis is the student’s protagonism. The methodology used was the bibliographic analysis on the social function of the school and the formation of the student as a protagonist, among them: Masschelein and Simons (2017), Goulart (2017) and Pasquali (2017). Socioemotional Skills and the Life Project for High School Students are also addressed. (Brazil, 2018). The results show that the highlighted proposal brings as a central point the development of socio-emotional skills within the curriculum in a mandatory way, in the action called Life Project for High School Students, which mobilizes the school, responsible for the integral formation of the subject, to resize its Pedagogical Political Project and its educational process to incorporate actions of this nature.